HEALTH BELIEF MODEL DAN KAITANNYA DENGAN KETIDAKPATUHAN TERAPI ANTIRETEROVIRAL PADA ORANG DENGAN HIV/AIDS (Unnes Journal of Public Health, 2017)
Antiretroviral (ARV) therapy for people living with HIV/AIDS (PLHIV) may reduce mortality and improve the quality of life among them. Non-adherence of HIV/AIDS patients in ARV therapy may lead to cease of therapy, increase risk of death, complicate evaluation of ARV services, and increase the risk of ARV resistance if they wish to start over. This study aimed to determine the factors that cause non-adherence to ARV therapy among PLHIV in Pemalang Regency. The research used qualitative method with case study approach. Data collection was conducted through in-depth interviews, observations, and documentation to 6 HIV/ AIDS patients who were listed as non-adherence patient in ARV therapy. Data analysis was done descriptively with triangulation method and data analysis. Results revealed that the factors that cause non-adherence to ARV therapy among PLHIV were lack of vulnerability perception to illness in the future, lack of illness perception among informants about the severity of illness, lack of benefit perception perceived by most informants, and barrier perception of side effects, lack of facilities to access ARV, and pudency that their HIV-positive status was known by others.